Penguatan Moderasi Beragama melalui Keterlibatan Mahasiswa KKN UINSU 2025 dalam Tradisi Adat Karo di Desa Gurukinayan, Kecamatan Payung, Kabupaten Karo - Pangulu Abdul Karim; Muhammad Segara Husmawan; Afifi Takrimi Lubis; Nazwa Dwi Harika; Sonya Noprisa Sumantri; Najwa Felisha Lubis; Nurul Adila Rambe; Annisa Aulia Putri; Tiara Azura; Kasia Yuliana Barutu; Nur’aida Nabila; Ahmad Rifki Saragih (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Religious moderation is one of the priority programs in strengthening religious life in Indonesia. The Community Service Program (KKN) students of Universitas Islam Negeri Sumatera Utara (UINSU) 2025 play an important role in implementing the values of religious moderation through socio-cultural approaches. This article discusses the involvement of UINSU KKN students in Karo traditional practices in Gurukinayan Village, Karo Regency, as an effort to strengthen tolerance, respect local wisdom, and build interfaith dialogue. This study employs a descriptive qualitative approach using observation, interviews, and documentation techniques. The findings show that student participation in traditional activities such as customary ceremonies, mutual cooperation, and cultural dialogue has successfully created a harmonious space for interfaith encounters. This illustrates that the integration of Islamic values as rahmatan lil ‘alamin with local wisdom can strengthen religious moderation. Moreover, student involvement demonstrates how social interaction can serve as a medium of character education that instills empathy, respect for differences, and willingness to collaborate across religious and cultural boundaries. This experience also encourages students to become agents of social change capable of linking Islamic values with local realities. The findings further emphasize the importance of collaboration between universities, traditional leaders, village authorities, and religious figures in creating social harmony. Thus, KKN is not only understood as a community service program, but also as a strategic medium to cultivate a culture of peace, strengthen social solidarity, and preserve local traditions amidst modernization and globalization.